Trastornos del sueño en el paciente adulto hospitalizado - Aguilera O., Ledda; Díaz S., Mario; Sánchez G., Haroldo (Revista Hospital Clínico Universidad de Chile, 2012)
Hospitalized adult patients frequently have sleep complaints. The majority of studies have principally focused in ICU patients. However, many medical and surgical disorders can disrupt the normal sleep architecture. Sleep disorders in hospitalized patients are susceptible to be successfully treated with hypnotics and control of ambient factors. We reviewed papers published in the Medline between 1997 – 2012, those considered relevant are be discussed in this review.